O ativismo ambiental nas ações e instalações de Siron Franci, 1986-2008: A arte como estratégia de divulgação - BERTAZZO, Lucia (2009)
Siron Franco is an artist who has, in a parallel with his pictorial work, always produced pieces that denounced social grievances and pieces of political nature which, placed in public settings, aimed at inducing the media to broadcast protests. The artist has for very long championed the environmental cause, what has led him to produce a series of pieces on the theme: paintings, demonstrations, stickers, installations, video-sculptures. This dissertation sets out to review the historical moment in which these pieces come out and presents them as postmodern art work produced in line with environmental activism. This research intends to analyze the insertion of artistic protests which have the environment as a cause, into the press and in contemporary art production